What are the factors associated with educational achievement for children in kinship or foster care: A systematic review. (August 2017) - O'Higgins, Aoife; Sebba, Judy; Gardner, Frances
Abstract: Children in care lag behind their peers on a number of outcome measures, including education. Interventions have been developed to help them close the gap with their peers but these have had limited success to date. One possible reason for this may stem from our lack of understanding about underlying processes and mechanisms. This paper presents the findings of a systematic review of the factors associated with educational outcomes for children in foster and kinship care. It aims to inform the literature on risk and protective factors and inform the development of future interventions. Eight major databases and websites were searched between 1990 and 2016 using a combination of mesh terms. Studies were included if they tested the statistical association between any variable and educational outcomes for school age children in foster or kinship care in high-income countries. Children in other placement types were excluded. Titles and abstracts were screened for 7135 studies identified through searches. Full texts were obtained for 298 and 39 were retained for inclusion. Over 70 factors were identified. For the purposes of the narrative synthesis, factors were categorised into spheres of influence adapted from Bronfennbrenner's (1979) ecological framework. The findings reveal significant heterogeneity. Male gender, ethnic minority status and special educational needs were consistent predictors of poor educational outcomes, while carers' and young people's aspirations appeared to predict greater success. The findings are discussed with implications for future research and practice. Highlights: Systematic review identified 39 studies and 70 factors tested for association with educational outcomes of children in foster or kinship care Significant heterogeneity in study findings reflects complex realities of children in care Male gender, ethnic minority status and special educational needs were consistent predictors of poor educational outcomes Carers' and young people's aspirations appeared to predict greater success